Total Quality Management In Nokia Mobile Phones Pty. Ltd. - Bains, Sharonjit Kaur (2005)
This research aims to provide a framework for analyzing the relationship between all TQM strategies implemented in Nokia Mobile Phones Pty. Ltd. This study does not only aim to analyze the current level of customer satisfaction with Nokia products but also analyze the effectiveness of quality control tools utilized by the company in providing world class customer service to its customers.